Pengajaran Bahasa Arab Berbasis Metode Tata Bahasa Leksikal (al-Naḥw al-Mu‘jamī) - Rahman, Zaim Najibuddin; Wahab, Muhbib Abdul (Department of Arabic Education - Faculty of Educational Sciences, 2024)
This article explores the application of lexical grammar (al-naḥw al-mu'jamī) in Arabic language teaching in Indonesia through the integration of the mind mapping-based PAIKEM model. This descriptive-analytical qualitative research examines the literature on lexical-grammatical theory and the contextual needs of learning in Indonesia, including curriculum analysis, teaching materials, and interviews with teachers. The results show that this method is able to overcome grammatical-lexical fragmentation by: (1) integrating top-down and bottom-up approaches for holistic understanding; (2) improvement of language fluency and accuracy from the beginning of learning; and (3) reduced reliance on internal translations. The main challenges include pedagogical readiness of teachers and adaptation of materials according to the local context. Through mind mapping-based PAIKEM, the research proposes a creative learning framework that combines lexical-grammatical structures with contextual activities, while emphasizing its flexibility in responding to individual learning styles. This study is the basis for the development of Arabic teaching methods that are more adaptive and oriented to the needs of Indonesian learners.